mu SR studies of the flux vortex phases in a BEDT-TTF superconductor - Pratt, F; Lee, S; Aegerter, C; Ager, C; Lloyd, S; Blundell, S; Ogrin, F; Forgan, E; Keller, H; Hayes, W; Sasaki, T; Toyota, N; et al. (2001)
mu SR has been used to probe the structure and stability of the flux vortex array in the organic superconductor kappa-(BEDT-TTF)(2)Cu(SCN)(2), At temperatures below 5 K and fields below 5 mT the internal field distribution is found to closely match that expected for a three dimensional (3D) Abrikosov flux line lattice (FLL). Careful studies in this 3D-FLL regime have enabled an improved measurement of the temperature dependence of the superconducting penetration depth to be made. A linear term is found in the temperature dependence of the penetration depth, suggesting the presence of line nodes in the gap parameter and d-wave pairing.